Anatomy Cadaver as a "First Patient" Experience - Lisa Granville; Suzanne Baker (Association of American Medical Colleges, 2014)
Abstract The 2008 Institute of Medicine report advocated that healthcare professionals integrate geriatric content into medical training to prepare for the rapidly increasing geriatric population and its impact on all aspects of health care. In addition, physicians and educators are encouraged to integrate basic science and clinical content into medical education. Given the fact that the average cadaver age is 73-years-old, we created this "first patient" introduction to identify and building upon the connections between human anatomy and physical diagnosis skills, and incorporate the age of the cadaver as a geriatric learning opportunity. This resource includes a facilitator's guide for a 15-20 minute small-group exercise during the anatomy class' unveiling of the cadaver. Clinical faculty introduce students to their first patient, the cadaver, and teach students how to investigate the patient's clinical history. Students thoroughly inspect the patient's surface anatomy and discuss the relevance of physical findings as attributable to normal aging or common age-associated conditions. Students also discuss their ideas on the clinical implications of findings on the patient's daily life: symptoms, functional impact (i.e., ADLs, IADLs, and AADLs) and possible means of compensation.